2015
DOI: 10.1103/physreva.91.023825
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional complex parity-time-symmetric photonic structures

Abstract: We propose a simple realistic two-dimensional complex parity-time-symmetric photonic structure that is described by a non-Hermitian potential but possesses real-valued eigenvalues. The concept is developed from basic physical considerations to provide asymmetric coupling between harmonic wave components of the electromagnetic field. The structure results in a nonreciprocal chirality and asymmetric transmission between in-and out-coupling channels into the structure. The analytical results are supported by a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…One of most promising applications of the idea is to use the PT-localization property to regularize the fields in broad aperture lasers, in particular in VCSELS. Broad aperture lasers, especially the semiconductor lasers, are known to result in spatial pattern formation 15,16 , which usually is undesirable effect from the technological viewpoint. Different techniques to regularize the spatial structure of the emitted field are proposed, in particular the spatial modulation of the amplifying media 17 .…”
Section: Discussionmentioning
confidence: 99%
“…One of most promising applications of the idea is to use the PT-localization property to regularize the fields in broad aperture lasers, in particular in VCSELS. Broad aperture lasers, especially the semiconductor lasers, are known to result in spatial pattern formation 15,16 , which usually is undesirable effect from the technological viewpoint. Different techniques to regularize the spatial structure of the emitted field are proposed, in particular the spatial modulation of the amplifying media 17 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a few recent studies of multidimensional PT-symmetric systems have demonstrated intriguing properties not found in 1D PT-symmetric systems, such as conical diffraction, third-order EPs, continuous rings of EPs, and rotating input by asymmetric coupling between wave vectors [14,[93][94][95][96][97][98]. Most recently, Fan et al considered 2D PT-symmetric PhCs, whose non-Hermitian primitive cell is an integer multiple of the primitive cell of the underlying Hermitian system [15].…”
Section: Unidirectional Reflectionless Propagation In Pt-symmetric Symentioning
confidence: 99%
“…Based on the PT concept several types of extended systems included PT gratings, PT lattices, and PT -symmetric resonant structures characterized by the complex-valued periodic functions have been studied both theoretically and experimentally [16][17][18][19]. The periodic systems also provide asymmetric response, offering for example a unidirectional invisibility [7], unidirectional coupling [20], and other peculiar effects. Due to periodicity such systems are resonant, i.e., provide the asymmetric responses in the vicinity resonant wavelength λ ∼ 2a, where a is the period of the structure.…”
Section: Introductionmentioning
confidence: 99%